Estratégias de marketing e as dimensões de valor da marca no transporte aéreo analisadas sob a perspectiva do passageiro - Oliveira , Denise Santos de (2017)
The purpose of this study is to examine the influence of the passenger's perception of the marketing strategies, developed by airlines, on each of their brand equity dimensions. From systematic review and research with airline managers a conceptual model was proposed, relating the marketing strategies, adopted by airlines, and the dimensions of consumer-based brand equity: brand associations/brand awareness, perceived quality and brand loyalty. The data were collected at six airports located in the Midwest, South and Southeast regions of Brazil and analyzed with Structural Equations Modeling (SEM). The results demonstrate correlation between the perception of marketing strategies, adopted by the airlines, indicating that for companies to affect the dimensions of value that the passenger perceives in the brand, it is not enough to carry out isolated investments, in one or the other strategy, but efforts to strengthen joint service innovations, price-related promotions and event sponsorship. This study provides a basis for the development of future studies on passenger-based brand equity and enables the best targeting of marketing strategies in the air transport sector